Influence of a surface condition on a microindenting parameters - Борисов, Д.І. (Proceedings of National Aviation University (archive), 2005)
Results of local nanoindenting of the aluminum alloy D-16АТ surface with the clad layer and without it are submitted under different surface conditions. It is shown, that the polishing of the clad material does not induce essential internal stresses in one.